RANCANG MODEL PENGEMBANGAN LAHAN BERBASIS AGROSILVOPASTUR DI KABUPATEN LEBONG - , TRIO SANTOSO, S.HUT, Prof. Dr. Ir. M. Sambas Sabarnurdin, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Limitations of land cultivation, steep topography, fertilizer shortages, low crop yields, stagnant cattle exploitation that occurs in Lebong District has prompted the opening of new land and a massive illegal logging in forest areas. Agrosilvopastur plus a simple application of biogas reactors can be a solution so that ne imidiate studies on the condition of cattle breeding, cultivation of land cultivation and characteristics of the community as a first step to plan agrosilvopastur an appropriate model to be developed. cultivations land were analyzed with The experiment was conducted with interviews and measurements on the 30 families of respondents. Map of the respondents digitizing contour length as the basis for the calculation of the potential of forage, the capacity of cows, cow manure, biogas, sludge and business analysis. potential and t The results showed he limitations in developing agrosilvopastur. The potential were long experience of farming with adequate land area and the large number of family members. While the weakness were the limitations of knowledge and capital in the form of dairy farms and the low education and income levels lead to the emergence of a variety of obstacles collecting forage and nutrition necessity. There are two models agrosilvopatur that can be applied, namely: MA1 and MA2. MA1 (25% - 40% land slope) have annual potentions : 45997.50 Â± 2907.30 total HMT Kg.Ha -1